ChemInform Abstract: Unusual Reactions of 6‐Amino‐1, 3‐dimethyluracil with Some Aliphatic Aldehydes. Issue 1 (17th December 2015) - Azev, Yurii A.; Ermakova, Ol'ga S.; Gibor, Alexey M.; Ezhikova, Marina A.; Kodess, Mikhail I.; Berseneva, Vera S.
Abstract: The reaction of 6‐amino‐1, 3‐dimethyluracil (I) with aliphatic aldehydes (II) in formic acid yields two products (IV) and (V).